Highly Efficient Synthesis of Digoxin - Liu, Hui; Zhou, Si-Yu; Liao, Jin-Xi; Tu, Yuan-Hong; Sun, Jian-Song (Synlett, 2021)
Taking advantage of the reliable stereocontrol capability of DMNPA group via long-distance-participation (LDP) effect as well as the mild and efficient deprotection conditions, the first and highly efficient synthesis of digoxin was achieved through a nine-step longest linear sequence with 41% overall yield.
Keywords: digoxin; cardiac glycosides; synthesis; glycosylation; DMNPA